A low standby power consumption AC/DC converter with exponential compensation. (July 2017) - Chang, Changyuan; Li, Yuanye; Jiang, Tianlin; Xu, Chunxue
Abstract: A flyback converter based on the two-stage exponential compensation is presented to reduce the system standby power consumption in this paper. The first-stage exponent circuit is achieved by RC integral circuit, and the waveform has a large slope at the beginning and it can close the power switch fast. The second stage exponent circuit is used to slow the rising trend of the exponent, especially before switching point, and makes the exponent circuit stop working after switching point. A proposed control IC has been fabricated in TSMC0.35 µm 5 V/600 V CMOS/LDMOS process. The experimental results indicate that the constant output voltage is 5 V, its precision is within ±4% and the standby power consumption is reduced by 30% in a wide range of universal input ac voltage from 90 V to 260 V, the average efficiency of the system is 89%, the system standby power is only 22 mW at 90 V input voltage, which meets the standby power requirements of the latest energy star on the AC/DC converter.